Possibility to Identify Bullets and other Components of the Cartridges by Consideration on Barrels and Projectiles Types - Dzindzibadze, Giorgi (European Scientific Journal, ESJ, 2022)
There are three types of barrels - polygonal rifling, traditional (conventional) rifling, and smooth bore. Since the internal shape of each barrel is different, the projectiles passed in these barrels have different marks and some are more depicted than others. Identifying private signs is necessary for comparison. If such marks do not remain on the surface of the bullet, it will be unusable for the identification process, which is based on a comparison of general and individual marks. Although scientists have different opinions on this issue, some of them claim that it is possible to identify small shot fired from a smooth bore. This issue has been explored and reflected in this paper, and it is possible to conduct an identification research on bullets. The paper also focuses on the issues the expert should consider when identifying. It is probably clear to everyone that it is impossible to conduct research of this scale on objects (shots, pellets, plastic container) that do not have sufficient identification marks. A reasonable conclusion used in court as evidence should be based on a combination of durable individual barrel channel marks with other bullets or a combination of durable individual barrel marks of the experimental weapon. In some cases, the expert’s conclusion is used as direct evidence in court and a wrong conclusion can result in the conviction of an innocent person.